CASCON First Decade High Impact Papers on - CASCON '10 2010
DOI: 10.1145/1925805.1925815
|View full text |Cite
|
Sign up to set email alerts
|

An examination of software engineering work practices

Abstract: This paper presents work practice data of the daily activities of software engineers. Four separate studies are presented; one looking longitudinally at an individual SE; two looking at a software engineering group; and one looking at company-wide tool usage statistics. We also discuss the advantages in considering work practices in designing tools for software engineers, and include some requirements for a tool we have developed as a result of our studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(153 citation statements)
references
References 12 publications
4
147
1
1
Order By: Relevance
“…Using a combination of surveys, interviews, observations, and collecting tool usage statistics, Singer and colleagues found that software developers spend most of their time searching for information as well as reading documentation and source code [3]. Most empirical studies since then have focused on various specific aspects of software development, such as the collaboration and communication of developers [23], the typical activities and tools related to coding [22], as well as developers information needs [11] and comprehension of software [24].…”
Section: Developers' Work Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a combination of surveys, interviews, observations, and collecting tool usage statistics, Singer and colleagues found that software developers spend most of their time searching for information as well as reading documentation and source code [3]. Most empirical studies since then have focused on various specific aspects of software development, such as the collaboration and communication of developers [23], the typical activities and tools related to coding [22], as well as developers information needs [11] and comprehension of software [24].…”
Section: Developers' Work Practicesmentioning
confidence: 99%
“…A software developer's work day might be influenced by a wide variety of factors such as the tasks being performed, meetings, interruptions from co-workers, the infrastructure or the office environment (e.g., [1], [2], [3]). Some of these factors result in activity and context switches that can cause fragmented work and that can have a negative impact on the developer's perceived productivity, progress on tasks, and quality of output (e.g., [4], [5]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Search and information seeking behavior of software developers has been studied quite extensively in the past (Sillito et al 2006;Ko et al 2006Ko et al , 2007Singer et al 1997;Murphy et al 2006;Sim et al 1998). However, there have been very few studies on search behavior of developers in Internet-Scale code search engines.…”
Section: Related Workmentioning
confidence: 99%
“…Searching for source code constitutes a significant part of a software development activity (Singer et al 1997;Murphy et al 2006). Software developers use a variety of tools to search source code that range from conventional tools such as 'grep' to advanced search facilities in integrated development environments.…”
Section: Introductionmentioning
confidence: 99%